BIO-INSECTICIDAL ACTIVITY OF CORIANDER (CORIANDRUM SATIVUM) LEAVES POWDER AGAINST COWPEA BRUCHID (CALLOSOBRUCHUS MACULATUS (FABRICUS) COLEOPTERA: CHRYSOMELIDAE) ON STORED CHICKPEA (CICER ARIETINUM (L.) (WALPER) - Bukar, Ahmadu; Dawud, Amina M.; Kumshe, Isa B.; Mohammed, Zubairu (FUDMA Journal of Sciences, 2025)
Laboratory experiment was carried out to assess the insecticidal activity of coriander leaves powder against Callosobruchus maculatus (F.). The leaves powder were applied at 1.0, 1.5, 2.0, 2.5 and 3.0 g/kg of chickpea and the 0.0g/kg untreated seeds served as control. The experiment was laid out in a Complete Randomized Design with six treatments replicated three times. Data collected were adult mortality, oviposition rate, F1 progeny emergence, seeds damage, weight loss, weevil perforated index and seeds germination were carried out. Significant difference (P
Keywords: Chickpea; Coriander; Callosobruchus Maculatus; Mortality; Oviposition